2012
DOI: 10.1002/app.37694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selective location of carbon nanotubes on electrical properties of thermoplastic vulcanizates

Abstract: Three types of conductive thermoplastic vulcanizates (TPVs) were prepared by blending polypropylene (PP), carbon nanotubes (CNT), and carboxylic acrylonitrile butadiene ultrafine full‐vulcanized powdered rubber (xNBR‐UFPR). The CNT locations were different in these three types of TPVs, i.e., CNTs were localized in PP matrix, in the xNBR‐UFPR phase, or mainly in the interface. It had been found that TPV with CNTs localized mainly in the interface had the lowest conductive percolation threshold among these three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…3(b)). However, when the CNTs are mainly located in the dispersed xNBR phase, it is difficult for the CNTs to form continuous paths for electron transfer [113].…”
Section: 4 2 2 4 S E L E C T I V E D I S P E R S I O Nmentioning
confidence: 99%
“…3(b)). However, when the CNTs are mainly located in the dispersed xNBR phase, it is difficult for the CNTs to form continuous paths for electron transfer [113].…”
Section: 4 2 2 4 S E L E C T I V E D I S P E R S I O Nmentioning
confidence: 99%
“…The sample prepared by Method I displayed the highest σ AC (0.04 S m −1 ). This value is almost 10 orders of magnitude higher than that reported by Zhu et al for the conductive TPV based on PP and the previously crosslinked xNBR loaded with similar amount of CNT 27 . By using the PP/CNT masterbatch approach, the conductivity decreased, due to the formation of CNT agglomerates, thus decreasing the chance of the formation of effective conductive pathway.…”
Section: Resultsmentioning
confidence: 56%
“…Despite several important studies involving this TPV, very few papers in the open literature reported its use to develop conductive TPV, to the best of the authors' knowledge. Zhu et al described the use of carboxylic acrilonitrile butadiene previously vulcanized as an ultra‐fine full‐vulcanized powder (xNBR‐UFPR) in PP matrix loaded with CNT prepared by traditional melt blending instead of DV 27 . In this study, the authors reached conductivity values of around 4 × 10 −3 S cm −1 with 2 phr of CNT.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Block copolymers and blended materials are two important parts of TPEs. Representative blended TPEs are thermoplastic vulcanizates (TPVs) obtained by blending thermoplastic and rubber. This method is so commercial that some of these materials have been applied by manufacturers.…”
Section: Introductionmentioning
confidence: 99%